The ego in psychedelic drug action: ego defenses, ego boundaries, and the therapeutic role of regression - Buchborn, Tobias; Kettner, Hannes S.; Kärtner, Laura; Meinhardt, Marcus W. (Frontiers in neuroscience, 2023)
The ego is one of the most central psychological constructs in psychedelic research and a key factor in psychotherapy, including psychedelic-assisted forms of psychotherapy. Despite its centrality, the ego-construct remains ambiguous in the psychedelic literature. Therefore, we here review the theoretical background of the ego-construct with focus on its psychodynamic conceptualization. We discuss major functions of the ego including ego boundaries, defenses, and synthesis, and evaluate the role of the ego in psychedelic drug action. According to the psycholytic paradigm, psychedelics are capable of inducing regressed states of the ego that are less protected by the ego’s usual defensive apparatus. In such states, core early life conflicts may emerge that have led to maladaptive ego patterns. We use the psychodynamic term character in this paper as a potential site of change and rearrangement; character being the chronic and habitual patterns the ego utilizes to adapt to the everyday challenges of life, including a preferred set of defenses. We argue that in order for psychedelic-assisted therapy to successfully induce lasting changes to the ego’s habitual patterns, it must psycholytically permeate the characterological core of the habits. The primary working principle of psycholytic therapy therefore is not the state of transient ego regression alone, but rather the regressively favored emotional integration of those early life events that have shaped the foundation, development, and/or rigidification of a person’s character - including his or her defense apparatus. Aiming for increased flexibility of habitual ego patterns, the psycholytic approach is generally compatible with other forms of psychedelic-assisted therapy, such as third wave cognitive behavioral approaches.